Four-year follow-up of LCAR-B38M in relapsed or refractory multiple myeloma: a phase 1, single-arm, open-label, multicenter study in China (LEGEND-2) - Zhao, Wan-Hong; Wang, Bai-Yan; Chen, Li-Juan; Fu, Wei-Jun; Xu, Jie; Liu, Jie; Jin, Shi-Wei; Chen, Yin-Xia; Cao, Xing-Mei; Yang, Yun; Zhang, Yi-Lin; Wang, Fang-Xia; et al. (Journal of hematology and oncology, 2022)
Background LCAR-B38M is a chimeric antigen receptor T cell product with two binding domains targeting B cell maturation antigen. Our previous reports showed a remarkable efficacy of LCAR-B38M in patients with relapsed/refractory multiple myeloma (RRMM) at a median follow-up of 2 years. Here, we report long-term safety and efficacy data from a median follow-up of 4 years. Methods LEGEND-2 was a phase 1, single-arm, open-label study conducted in four registered sites in China. Seventy-four participants with RRMM received LCAR-B38M treatment. Lymphodepletion was performed using cyclophosphamide or cyclophosphamide plus fludarabine. LCAR-B38M, at a median dose of 0.513 x 10.sup.6 cells/kg, was intravenously administered either in three split infusions or in a single infusion. The primary objective was the safety of LCAR-B38M, and the secondary objective was efficacy. Results As of May 25, 2021, the median follow-up was 47.8 months. All patients experienced [greater than or equal to] 1 adverse events (AEs). Grade [greater than or equal to] 3 AEs were observed in 45/74 (60.8%) patients. Cytokine release syndrome (CRS) occurred in 68/74 (91.9%) cases; 7 (9.5%) had grade [greater than or equal to] 3 CRS. One patient experienced grade 1 central nervous system toxicity. The overall response rate was 87.8%. Fifty-four out of 74 (73.0%) patients achieved complete response. The median progression-free survival was 18.0 months, and the median overall survival for all patients was not reached. The median duration of response was 23.3 months. Four patients experienced viral infection more than 6 months post-infusion, and four patients developed second primary non-hematological malignancies at a median time of 11.5 months post-CAR-T cell transfer. Conclusions The 4-year follow-up data of LCAR-B38M therapy demonstrated a favorable long-term safety profile and a durable response in patients with RRMM. Trial registration Clinicaltrials.gov NCT03090659 (retrospectively registered on March 27, 2017); ChiCTR-ONH-17012285. Keywords: Multiple myeloma, Chimeric antigen receptor therapy, B cell maturation antigen, Safety, Efficacy